2013
DOI: 10.1111/aas.12229
|View full text |Cite
|
Sign up to set email alerts
|

Fluid responsiveness predicted by elevation of PEEP in patients with septic shock

Abstract: In patients with septic shock, the absence of decrease in MAP during an elevation of PEEP may be used to identify patients who will not increase their cardiac output in response to fluid challenge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 47 publications
1
24
1
Order By: Relevance
“…Previous authors demonstrated that a brief "PEEP challenge" resulting in hypotension could predict fluid responsiveness. 36 To our knowledge, a similar strategy modifying tidal volumes has not been tried.…”
Section: Discussionmentioning
confidence: 99%
“…Previous authors demonstrated that a brief "PEEP challenge" resulting in hypotension could predict fluid responsiveness. 36 To our knowledge, a similar strategy modifying tidal volumes has not been tried.…”
Section: Discussionmentioning
confidence: 99%
“…During the last minute of high V T ventilation, measurements of the above-mentioned hemodynamic and respiratory variables, After the V T was returned to 6 ml/kg PBW and all of the hemodynamic variables had returned to baseline values (variations < 10%), VE was performed for 10 minutes using an infusion of 6% hydroxyethyl starch (HES 130/0.4, Volulyte; Fresenius Kabi, Stans, Switzerland) 6 ml/kg PBW. Two sets of measurements (HR, MAP, SVI, PV, PIP, Crs, PPV, and SVV) were performed before (T3, base 2) and 5 minutes after VE (T4) [28,29]. Percentage differences in ODM-derived SVIs before and after VE were used as principal indicators of fluid responsiveness.…”
Section: Study Protocolmentioning
confidence: 99%
“…Fluid responsiveness was investigated by means of transesophageal echocardiography in septic shock in three studies published in 2001 and in 2014, respectively, all assessing different parameters. Wilkman et al (13) observed that decreased in mean arterial pressure (MAP) due to an increased in peak end-expiratory pressure (PEEP) predicted fluid responsiveness (cut off value of ΔMAP for clinical use −8%) while Feissel et al (12), in a small subgroup of 19 patients with septic shock and preserved LV systolic function, observed that analysis of respiratory changes in aortic blood velocity was an accurate method for predicting the hemodynamic effects of volume expansion. Different parameters were assessed by Charbonneau et al (11) who observed that variations in superior vena cava diameters (ΔSVC) was significantly more accurate than changes in inferior vena cava width (ΔIVC) in predicting fluid responsiveness in 44 mechanical ventilated septic shock.…”
Section: Editorialmentioning
confidence: 99%